Who's Your DadA? d-Alanine Levels Regulate Bacterial Stiffness - Pascal D. Odermatt (American Society for Microbiology, 2018)
ABSTRACT A central question in mechanobiology is how cellular-scale structures are established and regulated. In bacteria, the cell envelope is essential for mechanical integrity, protecting against environmental stresses and bearing the load from high turgor pressures. Trivedi et al. (mBio 9:e01340-18, 2018, https://doi.org/10.1128/mBio.01340-18) screened a Pseudomonas aeruginosa transposon library and identified genes that influence cell stiffness by measuring cell growth while cells were embedded in an agarose gel. Their findings provide a broad knowledge base for how biochemical pathways regulate cellular mechanical properties in this pathogen. Dozens of genes across diverse functional categories were implicated, suggesting that cellular mechanics is a systems-level emergent property. Furthermore, changes in d-alanine levels in a dadA (d-alanine dehydrogenase) mutant resulted in decreases in the expression of cell wall enzymes, cross-linking density, and cell stiffness. These insights into the biochemical and mechanical roles of dadA highlight the importance of systems-level investigations into the physical properties of cells.